MANAJEMEN PESANTREN UNTUK MENINGKATKAN KETERAMPILAN BERBICARA BAHASA ARAB DI PONDOK PESANTREN DINIYYAH PASIA KABUPATEN AGAM - Ijah Kurniawati (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
This research aimed at describing the management of Boarding School Diniyyah Pasia on upgrading students’ speaking of Arabic language skill. This research belongs to qualitative case study. The results revealed that the management was good. The curriculum applied was determining on Arabic language skill in order to make good environment on speaking of Arabic skill. The instructional process of Islamic education used Arabic language for transferring knowledge.Keywords: Managemen, Arabic Language Skill, Boarding School, Agam.